Pengaruh Intelectual Capital Dan Kondisi Keuangan terhadap Kinerja Perbankan (Studi Pada Perusahahaan Perbankan Yang Terdaftar Di BEI Periode 2011- 2015)2011-2015) - Khoiriyah, Mifthakhul, Dr. Triyono, SE, M.Si, Imronudin, S.E, M.Si, Ph.D (2017)
The purpose of this study is to analyze the influence of intellectual capital and financial conditions against the Return On Assets (ROA) at banking company in Indonesia. This research use quantitative approach . The results of the study shows that Value Added Capital Efficiency (VACE) has significant negative effect against the Return On Asset (ROA), Value Added Human Capital (VAHU) has negative effect against the Return On Asset (ROA), Structural Capital Value Added (SCVA) has negative effect against the Return On Asset (ROA), the value of intellectual capital (VAIC_TM) does have not significant impact on Return On Asset (ROA). And the financial performance variables consist of operating expenses against the operating income (BOPO) significant negative effect against the Return On Asset (ROA), Net Interest Margin (NIM) positive significant effect against the Return On Asset (ROA), Capital Adequacy Ratio (CAR) of significant negative effect against the Return On Asset (ROA), Non Performing Loan (NPL) positive effect not significant against the Return On Asset (ROA), Loan to Deposit Ratio (LDR) positive effect not significant against the Return On Asset (ROA). Keywords: Intelectual Capital, Return on assets, Financial Performance.